Computationally efficient modelling of the fatigue behaviour of composite materials. (November 2015) - Stens, Christine; Middendorf, Peter
Highlights: We investigate the fatigue behaviour of carbon fibre reinforced plastics. A simple progressive damage model is implemented into FEA code. The behaviour is modelled using different combinations of classical lamination theory and FEA. The use of this combination reduces the number of FEA calculations over the lifetime. Simple tensile specimens are calculated as well as a cap profile. Abstract: Fatigue of composite structures is a complex process involving several types of failure. Existing approaches either neglect this complexity or require large computational effort. In this work, a simple progressive damage model including strength and stiffness degradation is implemented into finite element (FE) software. To reduce computational time, the major part of stress calculations is carried out by classical lamination theory. At single points of time, FE analysis is employed to support these calculations. The simplified model is tested against a reference model using FEA after each load cycle. Calculations are set up for a tensile specimen and a cap profile with quasi-isotropic layup. The simplified model using CLT is shown to be in good agreement with the reference while significantly reducing computational time.